Behaviorally and perinatally HIV-infected young women: targets for preconception counseling. Issue 3 (4th March 2017) - Echenique, Marisa; Rodriguez, Violeta J.; LaCabe, Richard P.; Privette, C. Kyle; Jones, Deborah L.; Potter, JoNell Efantis; Fischl, Margaret A.
ABSTRACT: This study aimed to describe demographic and psychological characteristics among HIV-infected young women, and to identify knowledge, attitudes, and behaviors associated with conception, with the goal of informing interventions or programmatic decisions regarding preconception counseling methods for young women living with HIV. Behaviorally and perinatally HIV-infected young women ( n  = 34) were conveniently sampled in Miami, Florida. Participants were asked to complete measures of reproductive knowledge, attitudes toward conception, and risk behaviors, as well as measures of depression and cognitive functioning. Perinatally and behaviorally HIV-infected young women were very similar in important areas of health preconception practices such as conception-related health literacy and conception-related communication with providers. Behaviorally infected women, however, were somewhat more likely to have been pregnant in the past, and had greater knowledge of healthy contraception practices and family planning. Despite the difference among groups, both the perinatally and behaviorally acquired women demonstrated having adequate overall knowledge. Depression was higher and consistent with moderate depression among the behaviorally HIV-infected women in comparison to perinatally infected women. This study found that that despite adequate reproductive knowledge, most young HIV-infected women were not using contraception. Given the consequences of presentation of advanced HIV during pregnancy, the need for both treatment adherence and preconception counseling is essential. Results suggest that interventions or programmatic decisions regarding preconception counseling methods for young women living with HIV are necessary and potentially transferrable between populations.